Career women's mental wellbeing in the era of population decline: the effects of working environment and family environment on the mental wellbeing - Zhou, Bowen; Wu, Xuchen; Ge, Ruixue; Zhuo, Dongni (Frontiers in Public Health, 2024)
Introduction In recent years, it has become increasingly evident that the population in many countries has been declining. China, which was previously the world's most populous nation and is often categorized as an emerging economy, officially entered an era of population decline in 2022. The advent of this era has make China's economic development more uncertain and aging of population more pronounced. To address the population decline, the Chinese government implemented the “Three-Child Policy” to encourage childbirth, aiming to reverse the negative population growth. However, this policy has not achieved the expected goals. Instead, it has increased the pressure on women to bear children, particularly for career women, where such pressure may conflict with their existing work and family environments, subsequently affecting their mental wellbeing. Methods A survey was conducted to investigate the mental wellbeing status of career women in Changchun City, Jilin Province, Northeast China. It analyzes the impact of working and family environments on the mental wellbeing of these women. Results Based on the survey, this study draws five conclusions: A. The mental wellbeing status of career women varies across different ages, industries, and childbirth statuses. B. The perceived adverse impact of childbirth on the working environment may negatively affect the mental wellbeing of career women. C. The perceived adverse impact of childbirth on the family environment may negatively affect the mental wellbeing of career women. D. Career women are not satisfied with the effectiveness of current policies in protecting women's rights. E. Compared to working environments, there is a greater demand for career women in the family environments, particularly in reducing various family burdens. Discussion The pro-natalist policies introduced in response to negative population growth can worsen the mental wellbeing of career women, while the deterioration of their mental wellbeing could further accelerate population decline. Given the current challenges, this study suggests that effectively improving the mental wellbeing of career women requires building psychological resilience among childless career women, reducing the burden of family on career women, and continuously improving policies and regulations that protect the rights of career women.